UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA MELALUI PENGGUNAAN MEDIA VIDEO PEMBELAJARAN BERBASIS POWERPOINT DI SMK NEGERI 2 SITUBONDO - DWI USTIK DIANA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2021)
This descriptive study aims to determine the motivation of learning achievement between learning using powerpoint-based learning videos and without using powerpoint-based learning videos.Comparatively aims to determine the difference in learning achievement of physics between powerpoint-based learning videos between powerpoint-based learning using learning and without powerpoint-based learning videos.This research is a quasi experimental conducted at SMK Negeri 2 Situbondo in 2020/2021. The results of descriptive research show that the tendency of learning achievement in physics taught using powerpoint-based learning video is in the very high category. The result of the analysis show that there is a significant difference in learning achievement between using powerpoint-based learning videos and without using powerpoint-based learning videos. The average achievement of learning physics using powerpoint-based learning videos is higher than learning without using powerpoint-based learning videos. So it can be concluded that learning using powerpoint-based learning videos is more effective than learning without powerpoint-based learning videos.